Kevätlinnuille etelässä - Merikanto, Oskar (säv.); Erkko, J. H. (san.); Ojanperä, Abraham (esitt.); Merikanto, Oskar (esitt.); Abraham Ojanperä (baritoni), Oskar Merikanto (piano) (1904)
Myös Gramophone 282755.
Keywords: yksinlaulut - Suomi - 1890-luku